Outcome of Conservative Versus Surgical Treatment of Humeral Shaft Fracture in Children and Adolescents: Comparison Between Nonoperative Treatment (Desault's Bandage), External Fixation and Elastic Stable Intramedullary Nailing. Issue 3 (April 2017) - Canavese, Federico; Marengo, Lorenza; Cravino, Mattia; Giacometti, Vanessa; Pereira, Bruno; Dimeglio, Alain; Origo, Carlo; Andreacchio, Antonio
Abstract : Background: The main objective of this study was to retrospectively evaluate the clinical and radiographic outcomes of displaced humeral shaft fractures in children treated by Desault's bandage (DB), external fixation (EF), and elastic stable intramedullary nailing (ESIN). Methods: During the study period, 36 consecutive children with displaced humeral shaft fracture were treated by DB (Group A), EF (Group B) or ESIN (Group C). All the patients underwent full-length preoperative and postoperative anteroposterior and lateral radiographs of the injured humerus. One year after the index surgery, patients were asked to answer the short version of the Disabilities of the Arm, Shoulder and Hand outcome questionnaire (Quick DASH). Results: Ten patients (27.8%) were in Group A, 11 (30%) in Group B, and 15 (41.7%) in Group C. Mean age at the time of injury was 10.8±2.3 years (range, 8 to 15.2 y), 11.7±2.5 years (range, 6.8 to 15.9 y), and 12.7±2.2 years (range, 6.9 to 15.3 y) in Groups A, B, and C, respectively ( P =0.08). Groups A, B, and C did not differ significantly in their demographics ( P >0.05). Surgical treatment (Groups B and C) provided a better radiologic outcome than nonoperative treatment (Group A) ( P =0.05). No statistically significant differences were observed for preoperative, postoperative and at last follow-up mean displacement between Groups B and C ( P >0.05). Overall, 9 of 36 patients developed a complication: 2 in Group A (20%), 4 in Group B (37%), and 3 in Group C (20.1) ( P =0.92). Mean Quick DASH score was 3±8.6 (range, 0 to 27.3), 1.4±2.9 (range, 0 to 9), and 1.2±4.7 (range, 0 to 18.2) in Groups A, B, and C, respectively. All the patients were able to resume previous physical and sport activities 4 to 6 months after the last fracture reduction procedure. Conclusions: Surgery is not contraindicated in children with displaced humeral shaft fractures. EF and ESIN provide a better radiologic outcome, less posttreatment pain and faster mobilization than DB. However, numerical differences, although statistically significant, were not clinically relevant for all variables but immobilization time. Nonoperative treatment was as efficacious as surgical treatment apart from the length of time for immobilization. Level of Evidence: Level III.